Establishing the reference intervals of plasma PLG, FXII activity, and FXIII antigen in healthy adults in Guangzhou - Zhenfei Zhang; Fang Wu; Zejie Zhou; Huixian Luo; Yuehua Qin; Meng Yang; Yinjuan Mo; Zhiqiang Zhu; Yi Zhang; Yonghui Guo (BMC Cardiovascular Disorders)
Abstract Objective To establish the reference intervals of plasma Plasminogen, Factor XII activity, and Factor XIII Antigen in healthy adults in Guangzhou. Methods A total of 168 young people (75 males and 93 females, aged 18–65 years) who underwent physical examination in Zhujiang Hospital of Southern Medical University from 2020 to 2022 were recruited. Sysmex CS5100 automatic coagulation analyzer and matching reagents were used to detect Plasminogen. Factor XII activity and Factor XIII Antigen were detected using the ACL TOP 700 (Instrumentation Laboratory, Bedford, MA, USA) automatic coagulation analyzer and matching reagents; reference intervals were established. Results Plasma Plasminogen and Factor XIII Antigen were normally distributed, and plasma Factor XII activity showed a skewed distribution with no statistical significance in gender. The established reference intervals were as follows: Plasminogen: 71.6-123.0%; Factor XIII Antigen: 55.1-113.1%; Factor XII: 42.3-144.1%. Conclusion The reference intervals for special coagulation items of the laboratory population in a particular area should be established to provide results that align with the population characteristics for assessing the coagulation status of clinical patients.